Synthesis, spectroscopic, structural and magnetic studies of new binary Cr(III)-citrate pH-specific structural variants from aqueous media - Gabriel, Catherine; Raptopoulou, Catherine P.; Drouza, Chryssoula; Lalioti, Nikolia; Sarifoglou, Athanassios (My University, 2009)
In an attempt to understand the aqueous interactions of Cr(III) with the low molecular mass physiological ligand citric acid, the pH-specific synthesis in the binary Cr(III)-citrate system was pursued, leading to the new complexes Na3[Cr(C6H5O7)2] ·8.5H2O (1) and (Hdmphen)6[Cr(C6H5O7) 2]·(NO3)3·14H 2O (2). Complexes 1 and 2 were characterized by elemental analysis, spectroscopic, structural, thermal, and magnetic susceptibility studies. The structures of 1 and 2 reveal a mononuclear octahedral complex of Cr(III) with two citrate ligands bound to it. Albeit of the same deprotonation state, the disposition of the two citrate ligands with respect to Cr(III) differs between 1 and 2 in the solid state, thus reflecting the presence of pH-structural variants in the requisite binary system. This conformational difference is lifted in aqueous solution, thus providing (a) comparative information on the distribution and diversity of species in the binary Cr(III)-citrate system, and (b) insight into the nature of interactions developing in the binary Cr(III)-hydroxycarboxylate systems in abiotic and biological applications
Keywords: Chromium--toxicity; Citrates; Magnetic susceptibility; Variants; X-ray telescopes